Transformasi Aktivitas K-Popers Di Media Sosial: Analisis Drone Emprit Dalam Framing Isu UU Cipta Kerja: Transformation Of K-Popers Activities In Social Media: Analysis Of Drone Emprit In Framing Issues Of Work Copyration - Sahrul Pora; Niken Nurmiyati; Tengku Imam Syarifuddin; Herdin Arie Saputra (JOURNAL OF GOVERNMENT SCIENCE, 2021)
The purpose of this study is to provide a more comprehensive understanding of K-Popers activities on social media against the framing of the 2020 Omnibus Law on Job Creation. This type of research applies qualitative approach. The method used is framing analysis with the Entman model to observe framing in two main dimensions, namely the collection and evaluation of problems or the importance of some aspects of reality/issues. The results of the research show that there have been widespread rejection of such a Job Creation Law in various regions in Indonesia, and K-Popers have emerged as supporting actors in the resistance movement. Several hashtags that later become trending topics cannot be separated from the role of fans of the South Korean music industry. K-popers play their role through social media in this issue by paying attention to what is happening (trending) in Indonesia.